Low level presence of genetically modified crops in food and feed trade in Malaysia - Andrew, Johnny (2019)
Genetic engineering technology has been applied extensively on crops. Although widely traded, the commercialization of genetically modified (GM) crops is subjected to domestic regulatory approval. Considering that the authorization processes are not synchronized across countries or better known as asynchronous approval, the mixture of authorized and unauthorized GM crops along the supply chain cannot be avoided. The possible implication is that GM crop authorized in one country might be found in another country that has not yet given authorization, thus creating a low level presence (LLP) situation. In light of this development, the research aimed to investigate these issues through its specific objectives.